Loyalitas Pelanggan RC Motogarage Bandung: Peran Pengalaman Pelanggan Dalam Masa Pandemi Covid-19 - Mesakh Abednego Setiawan; Daniel Hermawan (Coopetition : Jurnal Ilmiah Manajemen, 2022)
Customer experience is one indicator of the success of the services provided by the company. The concept of customer experience not only provides a unique experience, but is also positive, memorable, and creates long-term relationships. The study was conducted at RC Motogarage, a premium helmet shop in Bandung to analyze the role of customer experience in creating customer loyalty during the Covid-19 pandemic. This study aims to analyze the effect of customer experience on customer loyalty at RC Motogarage Bandung. This research uses quantitative methods with analytical descriptive types. Data collection techniques using a questionnaire. Sampling was done through purposive sampling as many as 112 respondents with the criteria of having visited and bought products at RC Motogarage Bandung. The results showed that the dimensions of Sense, Feel, Think, and Relate had a significant effect on customer loyalty at RC Motogarage Bandung, while the Act dimension did not significantly affect customer loyalty at RC Motogarage Bandung. Simultaneously, RC Motogarage Bandung succeeded in creating a customer experience during the Covid-19 pandemic.